ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN MEMPERTIMBANGKAN TOLERANSI RISIKO PADA SAHAM INDEKS KOMPAS100 PERIODE 2020-2022 - Sianipar, Yosua Yosafat; Tyas Danarti Hascaryani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this study is to determine the composition of the optimal portfolio on stocks indexed kompas100 based on risk tolerance through systematic risk. This study uses the CAPM and SIM models to form an optimal portfolio by considering risk tolerance through systematic risk. With the results there are 34 stocks in the kompas100 index that can be used as optimal portfolio candidates. And form 3 optimal portfolios based on high systematic risk, low systematic risk, and without considering systematic risk which then provides recommendations for investors in choosing the portfolio they like and expect.